Cross-Linguistic Metonymies in Human Limb Nomenclature - (:unkn) unknown (My University, 2014)
This dissertation is a cross-linguistic lexical study of metonymic change in human limb nomenclature. The data analyzed for this study make up both synchronic and diachronic databases. The synchronic data come from a sample of 153 non-Indo-European languages from 66 language families and are balanced for genetic and areal influence. The diachronic data are made up of a large collection of Indo-European etymologies. By comparing the metonymic patterns found in the Indo-European historical data with the synchronic cross-linguistic data, this dissertation explores to what extent the patterns of change found in Indo-European are cross-linguistic tendencies. In addition to showing how etymological data from one language family can help identify cross-linguistic tendencies, this dissertation also supports the claim that semantic change is regular, predictable and unidirectional. This serves as a framework for identifying cross-linguistic lexical tendencies. Along with its contributions to the theoretical discussion of regularity in lexical change, this dissertation proposes three universal tendencies and a substantial amount of lexical data that is useful for future cross-linguistic studies.
Keywords: Body Parts; Cross-Linguistic; Historical Linguistics; Human Limbs; Metonymy; Typology